The Edinburgh Companion to Women in Publishing, 1900-2020 - Battershill, Claire; Battershill, Claire; Bheacháin, Caoilfhionn Ní; Bird, Hazel Sheeky; Bold, Melanie Ramdarshan; Cesana, Roberta; Chambers, Matthew; Derrick, Stephanie L.; Fernández, Pura; Follacchio, Sara; Franco, Teresa; Heywood, Sophie; et al. (Edinburgh : Edinburgh University Press, 2024)
Explores the diversity of women's work in transatlantic and continental publishing across the twentieth-centuryThe first international edited collection to explore women's diverse work in book and magazine publishing in the twentieth century Specially commissioned, archivally-rich chapters from leading established and early-careers scholars, edited by an international research team Transatlantic and European/continental in focus, going beyond the Anglosphere, and modelling the best new comparative work in global print culturesCuts across aesthetic divisions in twentieth-century literary history and bridges the gap in understandings of women's contributions to publishing from first to second and third/fourth wave feminismsIncludes interviews with 8 contemporary women in publishing, plus new oral history researchWomen's creative labour in publishing has often been overlooked. This book draws on dynamic new work in feminist book history and publishing studies to offer the first comparative collection exploring women's diverse, deeply embedded work in modern publishing. Highlighting the value of networks, collaboration, and archives, the companion sets out new ways of reading women's contributions to the production and circulation of global print cultures. With an international, intergenerational set of contributors using diverse methodologies, essays explore women working in publishing transatlantically, on the continent, and beyond the Anglosphere. The book combines new work on high-profile women publishers and editors alongside analysis of women's work as translators, illustrators, booksellers, advertisers, patrons, and publisher's readers; complemented by new oral histories and interviews with leading women in publishing today. The first collection of its kind, the companion helps establish and shape a thriving new research field.
Frontmatter -- Contents -- Illustrations -- Acknowledgements -- Editors' note -- General Introduction Making Fields: Women in Publishing -- Part I Women as Editors and Publishers (Books) -- Introduction -- Voices: Interviews with Women in Contemporary Publishing -- 1 Black Women Publishers in the UK -- 2 Elizabeth Corbet Yeats and the Dun Emer Press: Irish, British and Transatlantic Connections -- 3 Women and Modernist Small Presses: Virginia Woolf, Anaïs Nin, Nancy Cunard, Caresse Crosby, Una Marson -- 4 'Mere girls': Grace Hogarth and Women Pathbreakers in Transatlantic Twentieth-Century Children's Publishing -- 5 Cultural Practices and the Public Arena: Contemporary Spanish and Latin American Women Editors -- 6 Democratising Culture and Building a New Consciousness: The Transformative Female Publishers of Post-Franco Spain -- 7 Translating and Publishing across the Channel: Natalia Ginzburg's Career from Einaudi to Carcanet -- 8 'I am not a cherry on top of the cake': Inge Schönthal Feltrinelli as Publisher -- 9 Toni Morrison at Random House -- 10 Intersectional Feminist Poetics at the Kitchen Table Press -- 11 Women of Colour in British Young Adult Fiction: Subverting Stereotypes and Expanding Identities -- Part II Women and the Periodical Press: Editors / Journalists /Activists -- Introduction -- Voices: Interviews with Women in Contemporary Publishing -- 12 'Unnamed but ever-present consulting editor': A Feminist Problem -- 13 The Expansive Vision of Jessie Redmon Fauset -- 14 A Literary Bridge between Italy and the United States: Ester, Natalia and Lea Danesi -- 15 Noémia de Sousa (1926-2002): Poetry, Gender and Journal Cultures -- 16 Periodical Publishing and the Independent Press: Nancy Chambers, Thimble Press and Signal: Approaches to Children's Books -- 17 Networks of Conflict and Mediation: Negotiating Socialist Feminism in the Second-Wave Periodicals Red Rag and Scarlet Women -- Part III Women Workers within Publishing -- Introduction -- Voices: Interviews with Women in Contemporary Publishing -- 18 Fitzi's Library: Feminist Bibliography and Anarchist Print Culture -- 19 Navigating Publishing in the 1930s: Gwenda David, Translator, Reader and Agent -- 20 Like Needle and Thread: How Women Connected Italy to America at the House of Farrar, Straus -- 21 Carmen Balcells: The Agent of the Latin American Literary Boom -- 22 Women's Creative Labour Contribution to the American Christian Publishing Industry -- 23 Women Literary Agents in Canada, 1950-2000 -- 24 Living the Dream: Feminist Book Publisher Memoirs and the Business of Anglo-American Feminist Life Writing in the Twenty-First Century -- Part IV Making / Selling / Distributing -- Introduction -- Voices: Interviews with Women in Contemporary Publishing -- 25 Women Editing and Illustrating in Popular Archaeology Publishing -- 26 A Room of One's Own on the High Street: Women Booksellers in Early Twentieth- Century Britain and the United States -- 27 Finding Miss Weaver: James Joyce and the Patron of Ulysses -- 28 Women in Type: Investigating Women's Role in Type Drawing Offices, 1910-1990 -- 29 Marie Neurath: Designing and Publishing Isotype Books for Children -- 30 Building Feminist Institutions: Women in Distribution, the Feminist Press and Cultures of Small Press Circulation -- 31 Virago Modern Classics: The Making of a Reprint Series -- 32 Murder at The Women's Press: Transnational Accomplices and the Feminist Crime Scene -- 33 Shifting Agency: Feminist Publishing Collectives in Aotearoa New Zealand -- Notes on Contributors -- Index -- Plate
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 06. Mrz 2024).
Available through De Gruyter.
Includes bibliographical references and index.
JSTOR
Keywords: Women publishers -- 20th century; Women publishers -- 21st century; Literary Studies; Éditrices -- 20e siècle.; Éditrices -- 21e siècle.; LITERARY CRITICISM / Feminist